A review of research hotspots and trends in biogenic volatile organic compounds (BVOCs) emissions combining bibliometrics with evolution tree methods. (28th December 2020) - Duan, Chensong; Zuo, Shudi; Wu, Zhifeng; Qiu, Yue; Wang, Jinfeng; Lei, Yanhui; Liao, Hu; Ren, Yin
Abstract: As ozone pollution in the troposphere has become increasingly severe, more publications have focused on the emissions of biogenic volatile organic compounds (BVOCs), which are important precursors for ozone formation. However, most reviews describe the research status of certain specific aspects rather than holistically quantifying research hotspots and development trends, which limit the overall understand of BVOCs emissions. In this paper, bibliometric analysis was used to study the publication output and hotspots of BVOCs emissions research from 1991 to 2019. Then, the evolutionary trends in BVOCs emission sources research were explored further by combining evolution tree and Markov chain methods. We found that the USA consistently took the leading position in BVOCs research, which cooperated with Germany and China closely. Environmental Science & Ecology and Meteorology & Atmospheric Sciences were the most active research subject categories. Current literatures mainly focused on the plant stress response, the atmospheric chemistry of BVOCs emissions, and their measurement by field determination and model-based estimation. Most publications researched BVOCs emitted by plants, in particular Pinaceae, while the growth of publications researching microbial volatile organic compounds (mVOCs) was slow. In the future, we should consider the role of mVOCs and combine field observation with model estimation to improve the credibility of BVOCs estimates and provide scientific guidance for air pollution control. And, with climate change, it will be worth exploring the driving variables of BVOCs emissions and its interaction in earth system to unravel how BVOCs emissions will respond to the changing earth system.